The Impact of Digitalization on Global Trade Law - Mira Burri (German Law Journal, 2023)
The Article explores the transformations triggered by digitalization in the domain of global trade law and seeks to evaluate the nature and the effects of the unfolding legal adaptation in this field of international law. For this purpose, the Article starts by mapping the sweeping effects of digitalization on trade and trade policies. It then turns to the current regulatory framework for digital trade—first, by sketching the state of affairs in the multilateral forum of the World Trade Organization (WTO) and second, by analyzing the more deliberate regulatory responses to the challenge of digitalization formulated in free trade agreements (FTAs), with a particular focus on some more recent advanced models of digital trade regulation. The Article finally seeks to contextualize and assess the impact of the existing legal framework and its adequacy for the contemporary data-driven economy, pointing also at some current deficiencies and potential setbacks going forward.